Prevention and treatment of colon cancer by peroral administration of HAMLET (human α-lactalbumin made lethal to tumour cells). Issue 1 (24th January 2013) - Puthia, Manoj; Storm, Petter; Nadeem, Aftab; Hsiung, Sabrina; Svanborg, Catharina
Abstract : Background: Most colon cancers start with dysregulated Wnt/β-catenin signalling and remain a major therapeutic challenge. Examining whether HAMLET (human α-lactalbumin made lethal to tumour cells) may be used for colon cancer treatment is logical, based on the properties of the complex and its biological context. Objective: To investigate if HAMLET can be used for colon cancer treatment and prevention. Apc Min /+ mice, which carry mutations relevant to hereditary and sporadic human colorectal tumours, were used as a model for human disease. Method: HAMLET was given perorally in therapeutic and prophylactic regimens. Tumour burden and animal survival of HAMLET-treated and sham-fed mice were compared. Tissue analysis focused on Wnt/β-catenin signalling, proliferation markers and gene expression, using microarrays, immunoblotting, immunohistochemistry and ELISA. Confocal microscopy, reporter assay, immunoprecipitation, immunoblotting, ion flux assays and holographic imaging were used to determine effects on colon cancer cells. Results: Peroral HAMLET administration reduced tumour progression and mortality in Apc Min /+ mice. HAMLET accumulated specifically in tumour tissue, reduced β-catenin and related tumour markers. Gene expression analysis detected inhibition of Wnt signalling and a shift to a more differentiated phenotype. In colon cancer cells with APC mutations, HAMLET altered β-catenin integrity and localisation through an ion channel-dependent pathway, defining a new mechanism for controlling β-catenin signalling. Remarkably, supplying HAMLET to the drinking water from the time of weaning also significantly prevented tumour development. Conclusions: These data identify HAMLET as a new, peroral agent for colon cancer prevention and treatment, especially needed in people carrying APC mutations, where colon cancer remains a leading cause of death.